The Response of Hemostatic Marker Levels to Activated Factor VII in a Neonate following Cardiopulmonary Bypass - Michael J. Eisses; Michael Richards; Denise Joffe; Jeremy M. Geiduschek; Wayne L. Chandler (Case Reports in Medicine)
The primary function of recombinant activated factor VII (rFVIIa) is to increase thrombin formation which leads to increased fibrin and less “bleeding.” As a result, most of literature utilizes “bleeding” as the outcome measure with respect to rFVIIa. However, we report the actual effect of rFVIIa on changes in hemostatic markers such as prothrombin activation peptide F1.2, thrombin antithrombin complex (TAT), D-dimer, tissue plasminogen activator (tPA), and plasminogen activator inhibitor (PAI) in a neonate after cardiopulmonary bypass. A single dose of rFVIIa caused a 5.5-fold increase in F1.2, 3.5-fold increase in TAT, and a small increase in d-dimer compared to only a 1.5-fold increase, no increase, and a decrease, respectively, in two neonates undergoing the same procedure having not received rFVIIa. The patterns of change for tPA and PAI were similar.